Enrichment of microbial communities for hexavalent chromium removal using a biofilm reactor. Issue 14 (30th September 2020) - Aoki, Masataka; Kowada, Taisei; Hirakata, Yuga; Watari, Takahiro; Yamaguchi, Takashi
Abstract: Given the toxicity and widespread occurrence of hexavalent chromium [Cr(VI)] in aquatic environments, we investigated the feasibility of a down-flow hanging sponge (DHS) biofilm reactor for the enrichment of microbial communities capable of Cr(VI) removal. In the present study, a laboratory-scale DHS reactor fed with a molasses-based medium containing Cr(VI) was operated for 112 days for the investigation. The enrichment of Cr(VI)-removing microbial communities was evaluated based on water quality and prokaryotic community analyses. Once the DHS reactor began to operate, high average volumetric Cr(VI) removal rates of 1.21–1.45 mg L-sponge −1 h −1 were confirmed under varying influent Cr(VI) concentrations (approximately 20–40 mg L −1 ). 16S rRNA gene amplicon sequencing analysis suggested the presence of phylogenetically diverse prokaryotic lineages, including phyla that contain well-known Cr(VI)-reducing bacteria (e.g., Bacteroidetes, Firmicutes, and Proteobacteria ) in the polyurethane sponge media of the DHS reactor. Therefore, our findings indicate that DHS reactors have great potential for the enrichment of Cr(VI)-removing microbial communities.